Sinergi Tokoh Masyarakat dan Agama dalam Meningkatkan Kualitas Pendidikan dan Keagamaan di Kampung Serdang Lor, Kota Serang - Najat, Syifaun; Yasir, Alan Maulana (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2024)
Serdang Lor Village, Serang City, Banten, is an example of strong synergy between social and religious figures in improving the quality of education and religion. This research explores their roles and contributions in formulating, implementing, and evaluating such programmes. Data was collected through focus group discussions with community and religious figures, as well as field observations. The findings show that this synergy has improved the quality of education and religion in the village. Serdang Lor Village, Serang City, Banten, is one of the examples of a community that demonstrates strong synergies between public figures and religions in improving the quality of education and religion. This article examines the role and contribution of people and religions in formulating, implementing, and evaluating educational and religious programmes in Serdang Lor Village. Data is collected through focus group discussions with people and religion figures, as well as field observations. The findings of the research show that social and religious figures play an important role in: 1) Identifying the needs of education and religion of communities; 2) Formulating programmes that meet those needs; 3) Motivating and mobilizing communities to participate in such programs; 4) Monitoring and evaluating the effectiveness of such programmes. The synergy between the social and religious figures has been conclusively effective in enhancing the quality of education and religion in the Serdang Lor Village. Their roles were found to be very significant through studies that involved focus group discussions with the community and religious figures, as well as field observations. They are involved in identifying community needs, formulating appropriate programs, motivating public participation, and regularly monitoring and evaluating the programs. This collaboration not only improved children's interest in learning and community participation, but also strengthened religious understanding and gotong royong spirit. The effectiveness of this synergy is based on public beliefs, effective communication, and the high commitment of both public and religious figures involved.